¿Cómo se cuenta una vida? El retorno de lo biográfico en la literatura rioplatense contemporánea - Judith Podlubne; Julieta Yelin (Cuadernos LIRICO)
The texts collected here address the thematic and formal variants that the telling of a life has taken on in the literature of the Rio de la Plata region in recent decades. They also trace the dialogues that these texts establish with a strand of contemporary thought that has placed life at the centre of its concerns, reconfiguring, in that very gesture, the articulations between body and writing, voice and letter, zoé and bíos. The question "how is a life told?" functioned as an invitation to explore the current state of "life writing" in the Río de la Plata; the answers offered by the articles provide a reflective and updated panorama of such writing, as well as a map of the strategies with which present-day critics confront the always rich and tense relationship between literature and life.